EFFECTIVE CLASSROOM MANAGEMENT TECHNIQUES - Ruziyeva Munisxon Komiljonovna, an English teacher at Tashkent Academic Lyceum No.2 of the Ministry of Internal Affairs of the Republic of Uzbekistan (SCIENCE AND INNOVATION IDEAS IN MODERN EDUCATION, 2024)
This article provides information about how to discover the keys to harmony in your classroom. We’ll explore pro tips for controlling student behavior, fostering positive relationships, managing documentation, tracking trends, and more. You’ll walk away confident and equipped to create a structured learning environment where students can thrive. Key words: classroom management, structured learning environment